Comparison of Various Infant Milk Substitutes with the Guidelines by European Society of Paediatric Gastroenterology, Hepatology and Nutrition: A Cross-sectional Study - Priya Jose; Nishanth Rajan; Sudiksha Prabhakar; Peter Prasanth Kumar Kommu; Lalitha Krishnan (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: When mother's milk is not available, Infant Milk Substitutes (IMS) must be supplemented with medical advice. Human milk can be digested easily because of the whey protein present in it and which is less in other animal milk. Considering this fact the manufacturers have attempted to make IMS as close to breast milk. Aim: To compare the composition of different IMS with breast milk, and with international guidelines given by European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN). Materials and Methods: A cross-sectional study was performed between April to May 2020, at a tertiary centre in Puducherry, India. Total 11 whey protein containing IMS brands that were commercially available in the Indian market for children aged up to six months were included in the study. The IMS for preterm babies and those without whey protein like hydrolysed milk, IMS with soya bean extract were excluded from the study. The details of IMS was collected and compared. The composition of the IMS was taken from the information provided by the manufacturer. The data was entered in Microsoft excel and was analysed using statistical software Statistical Package for the Social Sciences (SPSS) version 20.0. Results: With respect to calories, protein, fats and vitamins all IMS met the requirements. Nucleotide content exceeded in 18.1%. Sialic acid was added in 9% IMS. Iron content is more than the ESPGHAN requirement in 9% IMS. Conclusion: All the IMS were almost within the range advised by ESPGHAN. The children who fail to gain adequate weight can be given the brands with more calories. Babies with features of iron deficiency, can be given Brand VIII. For parents who cannot afford to buy the IMS with smart nutrients, they can choose the basic IMS which are of low cost, but meets the requirements.